(untitled) (Sindoro: Cendikia Pendidikan, 2025)
The present discussion in EFL classrooms is how grammar instruction can be integrated with students’ digital behaviour, particularly for learning future verb forms. Grammar vocabulary is frequently taught separately in Japanese language education, preventing learners from understanding how to use tenses meaningfully. This qualitative case study explored the incorporation of microblogging software (Twitter and Threads) in developing students’ grammar acquisition in senior high schools in Indonesia. Referencing Social Learning Theory and Multimedia Learning Theory, the study conducted classroom observations and semi-structured interviews with 36 students. Results indicate that real-time feedback, natural interaction, and multimodal input are effective for learners’ contextualised use of future, will, going to, and present continuous verb forms. Admittedly, informal language and digital distractions are potential limitations, but teacher scaffolding can offset these obstacles. The findings illustrate how social media, when pedagogically intervened, facilitates the development of grammatical competence and productive skills. This has significant pedagogical implications for language education, suggesting that integrating digital tools can enhance grammar instruction and student engagement.